2020
DOI: 10.1002/sstr.202000004
|View full text |Cite
|
Sign up to set email alerts
|

Interlocked Dual‐Network and Superelastic Electrospun Fibrous Sponges for Efficient Low‐Frequency Noise Absorption

Abstract: Traffic noise is a major source of urban noise pollution, with severe threats to the physiological and psychological health of humans. Fibrous sound absorption materials are extensively applied in the control of traffic noise pollution; however, the larger fiber diameters and monotonous internal structure of such materials result in poor low‐frequency sound‐absorbing properties or unsatisfied mechanical properties. Herein, a biomimetic and robust strategy to design ultrastrong and superelastic fibrous sound ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Previous efforts were focused on using cost-effective fibrous materials as the core components for constructing noise-absorber [4][5][6] . However, due to the inherent limitations of large fiber diameter (usually >5 μm) and low porosity (<60%), the fatal defects of poor absorption of low-frequency (typically <1000 Hz) noise that is easily produced by vehicles remain for the conventional microfibrous noiseabsorbing materials [7][8][9] . To address this problem, it is necessary to increase the thickness or density of the fibrous materials, while which in turn lead to large weights (>50 mg cm -3 ) and poor absorption of high-frequency noise [10][11][12] .…”
mentioning
confidence: 99%
“…Previous efforts were focused on using cost-effective fibrous materials as the core components for constructing noise-absorber [4][5][6] . However, due to the inherent limitations of large fiber diameter (usually >5 μm) and low porosity (<60%), the fatal defects of poor absorption of low-frequency (typically <1000 Hz) noise that is easily produced by vehicles remain for the conventional microfibrous noiseabsorbing materials [7][8][9] . To address this problem, it is necessary to increase the thickness or density of the fibrous materials, while which in turn lead to large weights (>50 mg cm -3 ) and poor absorption of high-frequency noise [10][11][12] .…”
mentioning
confidence: 99%
“…Besides, the sandwich structure effectively increased the internal interface of GCNAs, which enhanced the multistage re ection path of sound waves inside the material and thus successfully increased the sound energy consumption. 9 To con rm the outstanding noise reduction performance of the GCNAs, the NRC and corresponding areal density of the sandwiched GCNAs were compared with typical already reported and commercial noise reduction materials 19,27,63 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] However, due to the inherent limitations of large ber diameter (usually >5 μm) and low porosity (typically <60%), the fatal defects of poor absorption of low-frequency noise that is easily produced by vehicles remain for the conventional micro brous noise-absorbing materials. [7][8][9] To address this problem, it is necessary to increase the thickness or density of the brous materials, while which in turn lead to high weights (>50 mg cm -3 ) and decreasing consumption of high-frequency sound waves. [10][11][12] Moreover, the vehicle's space left for sound-absorbing materials is limited, and increasing the density will improve fuel consumption, which violates the principle of energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…The composite structure is porous and shows good sound absorption performance in the 800–2500 Hz frequency range. Zong et al [ 84 ] reported a fibrous sound absorption sponge with an interlocked dual-network-induced stable fluffy-stacked structure formed by PSU microfiber and PVDF nanofiber networks. The structure gives the fibrous sponge an excellent sound absorption property at low frequency, and its sound absorption coefficient could reach 0.93 at 1000 Hz.…”
Section: Electrospun Micro/nanofiber-based Porous Sound Absorption Ma...mentioning
confidence: 99%